Effects of diverging channel design cooling plate with oblique fins for battery thermal management. (January 2023) - Choi, Hongseok; Han, Ukmin; Lee, Hoseong
Highlights: Diverging channel design cooling plate with oblique fins is newly proposed. Thermal unbalance of the battery module is improved using the proposed design. Cell-to-cell temperature difference in the pack cooling is decreased by 19.07%. The pumping power to satisfy the temperature conditions is decreased by 67.8%. Abstract: In this study, the thermal and hydraulic performances of a battery thermal management system are investigated in terms of the design of the cooling plate. A diverging channel with oblique fins (DCOF) cooling plate is newly proposed to overcome the limitations of the conventional straight channel cooling plate. The diverging design is applied to control the coolant velocity and heat transfer area, with oblique fins inserted to enhance the heat transfer efficiency. A simulation model of the battery and cooling system is developed and experimentally validated. When the DCOF design is applied to the battery module, the temperature uniformity is improved in terms of the temperature difference and standard deviation. As the investigation is extended from the module to the battery pack, the temperature difference and temperature standard deviation in the battery module are improved by 19.07% and 27.14%, respectively. Considering the power consumption of the cooling system, as the thermal performance of the DCOF design and baseline design is maintained, the power consumption of the coolant pump of the DCOF design is significantly reduced by 67.8%.